The long-run and dynamic behaviors of wages, productivity and employment in Malaysia - Abdullah Yusof, Selamah (Emerald Group Publishing Limited, 2008)
Purpose – This paper aims to examine the long-run and dynamic behaviors of real wage-employment-productivity relationship, using Malaysian manufacturing data, and to determine which related labor theories are supported. Design/methodology/approach – Time-series econometric techniques, which include stationarity and cointegration tests, vector error correction model, impulse response function and variance decomposition, are applied to analyze the relationships of real wages, employment and productivity.